REVIEW OF DRUG DISTRIBUTION SYSTEM STRATEGY OF INPATIENT AT PROF. DR. MARGONO SOEKARJO HOSPITAL PURWOKERTO - Niluh Puspita Dewi; Gunawan Pamudji; Aris Widiastuti (Faculty of Pharmacy, Universitas Gadjah Mada)
Decree of Minister of Health Number 1197/menkes/SK/X/2004 about Standard of Hospital Pharmacy Service, states that the Hospital Pharmacy Service was integral part of hospital health care system which oriented to patient care, provision of drugs quality, clinical pharmacy services, which affordable for all levels of society. Departement of Hospital Pharmacy (IFRS) was the only division were fully responsible for the management and control of all pharmaceuticals and other medical supplies which circulated and used in hospitals. Therefore IFRS should make appropriate strategies that start with the analysis of internal and external environments known as SWOT analysis to formulate strategy that can be implemented in the service of the IFRS. The research carried out by primary and secondary data collection regarding IFRS and direct observation in field conducted by the researchers. Research can be determined which factors into strengths, weaknesses, opportunities and threats that exist on Inpatient Drug Distribution System, which then made the determination of alternative strategies to be applied by using SWOT analysis and matrix QSP. The research results showed that the calculation results of internal evaluation matrix, strengths value of Inpatient Drug Distribution System in IFRS was greater than the weaknesses value at 0.32. The results of external factor evaluation matrix also the probability value was greater than the threat value at 0.06. Therefore Drug Distribution System of Inpatient at Prof. Dr. Margono Soekarjo Hospital located in quadrant 1, which supports policy of aggressive growth. Selection strategy by QSP matrix obtained results to improve the quality and quantity of human resources at 7.01; to establish patient visite program, at 7.43; to improve service quality in order to be more competitive with other pharmacies and hospitals at 7.28; and implement UDD distribution system at 7.66.Keywords: SWOT Analysis, Drug Distribution System of Inpatient.